Conversion of CO2 into cyclic carbonate catalyzed by an N-doped mesoporous carbon catalyst. Issue 10 (29th July 2021) - Liu, Dan; Fu, Jinxia; Zhou, Kuo; Kang, Shimin; Cai, Zhuodi; Xu, Yongjun; Duan, Peigao
Abstract : Ammonium hydroxide is first used as a nitrogen source to synthesize N-doped mesoporous carbon spheres (N-MCSs). Using N-MCS800 as a catalyst, the TOF of the cycloaddition of CO2 with epichlorohydrin is 236 h −1 . Abstract : N-Doped mesoporous carbon spheres (N-MCSs) had been synthesized through a dissolve–reassemble pathway using ammonium hydroxide as both the nitrogen source and base catalyst. The BET surface area and pore volume of the N-MCSs were measured to be 1341 m 2 g −1 and 1.47 cm 3 g −1, respectively. The analysis results of XPS and CO2 -TPD indicated that the N element was successfully doped in the carbon matrix and provided basic sites to the N-MCSs. It was an effective, mono-component, halogen- and metal-free catalyst for the cycloaddition of CO2 with epichlorohydrin, and the TOF could reach 236 h −1 . The high catalytic activity of N-MCS800 was ascribed to the synergistic effect of the specific surface area and pyridine nitrogen. More importantly, N-MCS materials had good stability and reusability.